2007
DOI: 10.1007/s10517-007-0177-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of trajectories of eye, head, and hand movements for early diagnosis of Parkinson’s disease

Abstract: Relationships between eye, head, and hand movements in patients with stages I-II Parkinson's disease were studied using an original method. The tests for individual movements in patients and healthy individuals yielded similar results, while coordination test revealed significant differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…Parkinsonian syndrome is an example of how dysfunction of inhibition, which occurs on the level of subcortical structures, can induce saccadic disorders. 1 In a number of studies of patients with Parkinson disease saccadic disorders similar to those described in the present study were observed [16][17][18][19] It should be emphasized that in some cases HIE induced disorders of saccadic electrophysiological parameters were even more pronounced than in Parkinson's patients (in particular three HIE subjects with clearly expressed hypokinetic syndrome). In comparison with Parkinson's patients HIE subjects with hypokinetic syndrome were characterized by increased instability of the latent period of saccades in the coordinated test and a pronounced disturbance of gaze stabilization after termination of saccades that was manifested by tremor eye movement of different amplitudes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Parkinsonian syndrome is an example of how dysfunction of inhibition, which occurs on the level of subcortical structures, can induce saccadic disorders. 1 In a number of studies of patients with Parkinson disease saccadic disorders similar to those described in the present study were observed [16][17][18][19] It should be emphasized that in some cases HIE induced disorders of saccadic electrophysiological parameters were even more pronounced than in Parkinson's patients (in particular three HIE subjects with clearly expressed hypokinetic syndrome). In comparison with Parkinson's patients HIE subjects with hypokinetic syndrome were characterized by increased instability of the latent period of saccades in the coordinated test and a pronounced disturbance of gaze stabilization after termination of saccades that was manifested by tremor eye movement of different amplitudes.…”
Section: Discussionsupporting
confidence: 82%
“…The fourth level consists of different zones of hemispheric brain cortex: frontal, rear parietal and occipital lobes, prestriar cortex, additional eye movement fields, dorsolateral frontal eye field (Brodmann's area 8) and the posterior cingulate. Disorders in the oculomotor system have been investigated in patients with different syndromes: schizophrenia [10][11][12], attention-deficit/hyperactivity disorder [13][14][15], Parkinson's disease [16][17][18][19], and Alzheimer's disease [20]. However, data on HIE influence of saccadic eye movements are rather scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that, in PD patients, reaching movement is limited by decreased movement of the upper limbs due to akinesia or bradykinesia, decreased flexibility due to rigidity of the four limbs and trunk, and the impairment of postural reflexes associated with these decreases. Moreover, it has been reported that PD patients experience disorders in eye movement [1618] and coordination between the eyes and head with reaching movements [1921]. Presumably, decreased motility of the eyes, head, and neck due to PD may affect the ability to detect the accurate position of a target object in space.…”
Section: Introductionmentioning
confidence: 99%
“…However, most systems based on technology eye-tracking, for the successful operation require new methods of mathematical description of human eye-motor system (EMS) and special equipment for experimental research [5][6][7].…”
mentioning
confidence: 99%